Connecticut Green Bank : in pursuit of inclusive prosperity - Bourg-Meyer, Vero; DeCew, Stuart; Bovarnick, Ben (London : Yale School of Management, 2018)
On July 12, 2017, the Harvard Kennedy School of Government bestowed the prestigious Ash award in policy innovation, the "Nobel of policy," upon the Connecticut Green Bank for its role in "sparking the green bank movement." The Green Bank used financial structuring to attract private capital to clean energy projects. But back in Connecticut, trouble was brewing. A contingent of leaders in the State House were calling for both a raid of the organization's balance sheet, and a dramatic reallocation in its funding streams. How then could the Green Bank, whose mission rested on building trust, both insulate itself from the political winds from the north, and move toward a more sustainable funding model? The bank's management team needed to carefully consider how different funding structures would impact their mission to accelerate private investment in clean energy, create Connecticut jobs, promote energy security, and address climate change.
Originally Published InBourg-Meyer, V., DeCew, S., & Bovarnick, B. (2018). Connecticut Green Bank: In pursuit of inclusive prosperity. Yale SOM Case 18-016 New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Connecticut Green Bank; Clean energy investment -- Connecticut